2010
DOI: 10.1111/j.1467-7660.2010.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Mungiki, Vernacular Organization and Political Society in Kenya

Abstract: This article uses the concept of 'political society' as unfolded by the 'subaltern studies' in India to shed new light on present-day political actors and democratic transitions in Africa. It discusses the political practices and dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…But our primary focus has been on local perceptions, understandings, and articulations of experience -on the ways in which the residents of Amaoti and Pumwani with whom we interacted, and who participated actively in our research, have been thinking and taking action regarding the restrictions and possibilities in their lives. Also, the reflections we present do not follow from one single project of research, but from a series of consecutive, parallel studies, whose results have been published separately (Frederiksen 2000(Frederiksen , 2002a(Frederiksen , 2002b(Frederiksen , 2002c(Frederiksen , 2007(Frederiksen & 2010Frederiksen & Munive 2010;Kaarsholm 2005Kaarsholm , 2006Kaarsholm & 2009.…”
Section: Fieldwork and Participatory Research In Historical Perspectivementioning
confidence: 99%
“…But our primary focus has been on local perceptions, understandings, and articulations of experience -on the ways in which the residents of Amaoti and Pumwani with whom we interacted, and who participated actively in our research, have been thinking and taking action regarding the restrictions and possibilities in their lives. Also, the reflections we present do not follow from one single project of research, but from a series of consecutive, parallel studies, whose results have been published separately (Frederiksen 2000(Frederiksen , 2002a(Frederiksen , 2002b(Frederiksen , 2002c(Frederiksen , 2007(Frederiksen & 2010Frederiksen & Munive 2010;Kaarsholm 2005Kaarsholm , 2006Kaarsholm & 2009.…”
Section: Fieldwork and Participatory Research In Historical Perspectivementioning
confidence: 99%
“…It is probable that the Luhya student who responded that Maasai live in the hut and Luos live in the permanent house is basing his understanding on both media campaigns and his neighborhood's ethnic composition. Though ethnic identity and class are engaged here as distinct spheres, Frederiksen (2010) reminds us that, in Kenya Ethnic identification has constantly been challenged by intra-ethnic class divisions and confrontations -there has been little material common ground between poor, displaced Kikuyu squatters in Rift Valley, for instance, and elite Kikuyu business networks in Central Province. Across Kenya, however, this view of Maasai is quite pervasive, most likely due to the Maasai's commitment to maintaining autonomy despite government policy and persisting poverty as well.…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Some consider that the creation of 'youth' as a category in Africa is a post-colonial phenomenon promoted by ministries of 'Youth Sports and Culture' and youth wings of political parties, while being nowadays further underwritten by a global consumption-oriented youth culture (Frederiksen 2010(Frederiksen : 1078. Donor agencies consider youth a specific social category 'laden with risk and uncertainty ' (UNESCO 2004: 6).…”
Section: How Policies Identify Youthmentioning
confidence: 99%
“…Growing youth bulges and widespread unemployment are often associated with insecurity, urban social unrest and political instability (Urdal and Hoelscher 2009;Frederiksen 2010). 4 Thus, a 2003 UN Security Council mission to West Africa reported that: 'In every county visited, the mission heard about the problem of unemployment, particularly among young people, and how this was a perennial source of instability in West Africa.'…”
Section: Problems Images and Policy Aimsmentioning
confidence: 99%